The Neoliberalization of Higher Education: Paradoxing Students' Basic Needs at a Hispanic-Serving Institution - Schraedley, Megan K.; Jenkins, J. Jacob; Irelan, Molly; Umana, Megan (Frontiers in Sustainable Food Systems, 2021)
Millions of college students in the United States lack access to adequate food, housing, and other basic human needs. These insecurities have only been exacerbated in recent decades by the country's neoliberal approach to higher education, with disproportionately negative consequences for historically underserved populations (e.g., racial/ethnic minorities, low-income students, and first-generation college students). For each of these reasons, this study explores organizational paradoxes faced by students attending a Hispanic-Serving Institution (HSI) in southern California. Drawing upon 30 semi-structured interviews with undergraduates who self-identified as historically underserved, our three-stage conceptualization of the data analysis revealed three specific paradoxes: provision vs. dependence, sympathy vs. disassociation, and bootstrapping vs. unattainability. We conclude with practical and theoretical implications for alleviating the repercussions of neoliberal policies on today's college students.